Role of 5-ht(7) receptors in the long-lasting hypotensive response induced by 5-hydroxytryptamine in the rat - Terrón, José A (1997)
1. The receptor mediating the long-lasting hypotensive effect of intravenous (i.v.) 5-hydroxytryptamine (5-HT) in the rat was originally classified as 5-HT(1)-like. Since some pharmacological properties of this receptor are closely similar to those for the cloned 5-ht(7) receptor, the present study investigated the effects of several 5-HT receptor agonists and antagonists showing high affinity for the cloned 5-ht(7) receptor in pithed rats with artificially raised blood pressure. 2. I.v. bolus administration of 5-HT, 5-carboxamidotryptamine (5-CT), 5-methoxytryptamine, lisuride and sumatriptan to bilaterally vagotomized pithed rats pretreated with ketanserin (0.18 μmol kg(−1), i.v.), the diastolic blood pressure of which had been raised by a continuous i.v. infusion of methoxamine (60–80 nmol kg(−1) min(−1)), produced dose-dependent hypotensive responses; only 5-HT and 5-CT displayed similar maximum effects. In addition to mimicking the hypotensive action of 5-HT with a lower maximum effect, lisuride strongly antagonized the 5-CT-induced hypotensive responses thus suggesting a partial agonist effect. The rank order of hypotensive agonist potency was 5-CT >> 5-HT ⩾ 5-methoxytryptamine ⩾ lisuride >> sumatriptan. 3. In experiments with antagonists, i.v. treatment with metergoline (2.48 μmol kg(−1)), mesulergine (2.76 μmol kg(−1)), methysergide (2.13 μmol kg(−1)), lisuride (0.22 μmol kg(−1)), methiothepin (0.68 μmol kg(−1)), mianserin (10.6 μmol kg(−1)), or the atypical antipsychotic drugs, clozapine (11.0 μmol kg(−1)) or risperidone (78.0 nmol kg(−1)), produced significant rightward displacements of the dose-response curve for 5-CT in methoxamine-infused pithed animals pretreated with ketanserin (0.18 μmol kg(−1), i.v.); lisuride, methiothepin and risperidone behaved as non-competitive antagonists as they elicited a significant reduction of the maximum effect to 5-CT. In contrast, blockade of 5-HT(1), 5-HT(3) and 5-HT(4) receptors with i.v. propranolol (3.38 μmol kg(−1)), MDL-72222 (1.59 μmol kg(−1)) and GR125487 (1.91 μmol kg(−1)), respectively, did not alter 5-CT-induced hypotensive responses; ketanserin (0.18 μmol kg(−1), i.v.) failed to modify the dose-response curve for 5-CT in saline-pretreated animals. Lastly, inhibition of the prostaglandin-forming cyclo-oxygenase and nitric oxide synthase with indomethacin (14 μmol kg(−1), i.v.) and N(G)-nitro-L-arginine methyl ester (L-NAME, 120 μmol kg(−1), i.v.), respectively, had no significant effects on 5-CT-induced hypotensive effects. 4. Taken together, the present pharmacological data suggest that the long-lasting vasodepressor action of 5-HT in the rat involves activation of receptors closely similar to the cloned 5-ht(7) subtype. Since no evidence for an indirect mechanism could be obtained, these receptors may be primarily located in the vascular smooth muscle of the systemic resistance vessels. These findings represent further evidence favouring the functional role of the 5-ht(7) receptor.